Linear anti-jamming algorithm design for multi-channel optical fiber communication - Haichao Yu (PLoS ONE, 2026)
The multi-channel fiber optic communication network, crucial for long-distance digital signal transmission, faces linear interference from orthogonal frequency division multiplexing. To address the challenge of linear anti-interference in digital signal transmission, this paper integrates Discrete Fourier Transform and Wavelet Transform techniques to precisely identify and locate linear interference signals during the transmission process of Orthogonal Frequency Division Multiplexing systems, and then specifically suppress and mitigate them. Firstly, this paper transforms multiple subcarrier digital signals in multi-channel transmission into linear interference signals. For these interference signals, wavelet decomposition is performed using wavelet transform technology, decomposing the noise signals into coefficients at different levels. Wavelet coefficients that are either above or below the threshold values are sequentially subjected to thresholding processing, thereby achieving denoising. Finally, by combining DFT and WT, the DFT-WT-LAJ algorithm is proposed. This algorithm searches for linear interference signals by employing both DFT and DMFT algorithms, and filters out all reconstructed linear interference signals from the transmitted signals. Experimental data show that the algorithm controls the amplitude below 10 Hz, achieves a synchronization probability of 0.7 at a signal-to-noise ratio (SNR) of 35 dB, and maintains an interference-to-signal ratio above 31 dB, significantly enhancing signal quality and transmission reliability.